2012
DOI: 10.2340/16501977-0969
|View full text |Cite
|
Sign up to set email alerts
|

Influence of advanced prosthetic knee joints on perceived performance and everyday life activity level of low-functional persons with a transfemoral amputation or knee disarticulation

Abstract: Although Medicare Functional Classification Level-2 amputees report benefitting in terms of their performance from using an MPK, this is not reflected in their actual daily activity level after one week of using an MPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…Newer studies show that although patients with above knee amputation report benefitting from e.g. microprocessor-controlled prosthetic knee joints after one week of using them, this benefit is not reflected in their actual daily activity level [9]. Additionally the epidemiology may have impact on the satisfaction during motor performance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Newer studies show that although patients with above knee amputation report benefitting from e.g. microprocessor-controlled prosthetic knee joints after one week of using them, this benefit is not reflected in their actual daily activity level [9]. Additionally the epidemiology may have impact on the satisfaction during motor performance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Theeven and colleagues have been busy using and refining the ADAPT and publishing subsequent articles in 2011 13 and 2012 14 investigating the effects of MPK on K2-level amputees, interestingly using a US healthcare system code in an international setting. Microprocessor-controlled prosthetic knees have not been generally available to K2 functional level amputees, although some published research has shown that some K2 functional level amputees can improve to K3 with an MPK.…”
Section: Activities Of Living Measures Acclimation and Terrainmentioning
confidence: 99%
“…Theeven et al 14 also examined in detail 30 of these same prosthesis users' perceived performance enhancements when wearing MPKs versus NMPKs in the community using the Prosthetic Evaluation Questionnaire (PEQ). Although there was no improvement in activity during community ambulation as recorded by a waist-mounted accelerometer, there was a preference expressed for the MPK that offered both swing-and stance-phase control (C-Leg).…”
Section: Activities Of Living Measures Acclimation and Terrainmentioning
confidence: 99%
“…Some trials report no differences, 27,32 whereas others do find differences on variable subscales of the Prosthesis Evaluation Questionnaire. 26,41,170 All in all, there seems to be no univocal evidence for a positive effect of microprocessor-controlled prosthetic knees on prosthesis-related quality of life. On balance confidence we did not find differences.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,32,41,170 On performance based measures of mobility, studies reported increased walking speed on both even and uneven terrain, 26 decrease in time that was needed to complete the Timed "up & go" Test, 171 increased performance of ramp and stair de-scent, 27,32,36 and improved obstacle course navigation when walking with a microprocessor-controlled prosthetic knee. 33,35 Finally, studies found no differences in daily step count between prosthetic knee conditions.…”
Section: Introductionmentioning
confidence: 99%